Om N. F. S. Grundtvig og G. P. Brammer - Eskedal, Anders (Grundtvig-Studier, 2008)
Om N. F. S. Grundtvig og G. P. Brammer [Concerning N. F. S. Grundtvig and G. P. Brammer] By Anders Eskedal The hitherto unprinted letter here transcribed and commented was found among the works and papers left by Professor A. P. Thyssen. Dated 1824, it reveals a small and otherwise unknown correspondence concerning matters of business between Grundtvig and Gerhard Peter Brammer (1801-1884) who was to become (1830) principal of Snedsted pastoral college of education and (1845) Bishop of Aarhus. In his early years Brammer was acquainted with Grundtvig and much influenced by his theology. The article argues that despite disagreements and incompatibilities of temperament between Brammer and both Grundtvig and the Grundtvigians this influence was sustained throughout Brammer’s life. The whole of their correspondence in the years 1821-1825 is accounted for, in order to document both the context of the transcribed letter and the early relationship between Grundtvig and Brammer. The article then analyses the incident in 1824 which started the conflicts between Brammer and Grundtvig and the theological disagreements which finally led the two men into very different paths.